Cardiovascular risk assessment of pediatric dyslipidemic patients - Medeiros, A.M. (2012)
Identification of young population with high cardiovascular (CV) risk allows early intervention and prevention, delaying or abolishing occurrence of CHD in adult life. Hypercholesterolemia is an important CV risk factor that can be due to environmental or genetic causes. Genetic dyslipidemias, as Familial Hypercholesterolemia (FH), are associated with major risk of CV events.